Is the success of an issuer an investor success? Evidence from polish IPOs. Issue 1 (2nd January 2017) - Brycz, Bogumiła; Dudycz, Tadeusz; Kowalski, Michał J.
ABSTRACT: This article examines the factors that determine IPO success in raising equity capital, and how this success translates into investor success. The study is based on a sample of IPOs on the Warsaw Stock Exchange from 1998 to 2011. We find that pre-IPO profitability is a strong and positive signal for investors that translates into a higher offer price and therefore determines the success of the issuance. However, companies with high IPO success do not provide investors with better performance after going public, nor do they provide protection before the common phenomenon of long-term underperformance. A large-scale value migration between shareholders occurs in companies that achieve IPO success. The investor belief that pre-IPO profitability is a signal of the future earnings potential of an IPO firm indicates that they probably use simple heuristics and have a representativeness bias.